Comparsion of Liver and Spleen Elastometry Features - S. V. Morozov; V. А. Izranov (Вестник рентгенологии и радиологии)
The review presents data on the comparison of the features of liver and spleen stiffness measurements and those on the impact of various conditions on the measurement results (the type of a sensor used, food intake, number of measurements, patient position, breathing phase, etc.). Literature has been sought in the PubMed and eLibrary databases. In particular, the liver and spleen stiffness values vary differently at the height of inspiration and expiration. This is due to organ engorgement with a change in intrathoracic and intraabdominal pressures, as well as to a reduction in splenic arterial flow during exhalation. The review gives published data on liver and spleen stiffness values in healthy volunteers. The spleen is a stiffer organ than the liver. The different liver and spleen stiffness is explained by the features of blood supply (the spleen receives the most blood supply from the intensive-flow artery; the liver does from the portal vein). The reasons for increasing the stiffness of these organs in both health and disease are described. Estimation of liver stiffness can be used to diagnose cirrhosis and portal hypertension. That of spleen stiffness can help in the diagnosis of portal hypertension and in the indirect diagnosis of the presence of esophageal varices and the nature of a splenic lesion.